Green grinding-coassembly engineering toward intrinsically luminescent tetracene in cocrystals - Huang, Yinjuan (2022)
Developing an effective and green method toward organic functional cocrystals based on the solubility-mismatched coformers is highly desirable and very important. Herein, we applied a green two-step liquid-assisted-grinding coassembly (LAGC) in fabricating tetracene-octafluoronaphthalene (TC-OFN) cocrystals from solubility-mismatched pairs of tetracene (TC, poorly soluble, 0.2 mg mL-1) and octafluoronaphthalene (OFN, highly soluble, 0.2 × 104 mg mL-1). Such cocrystals are extremely difficult to prepare through the common solution-processing strategies. More importantly, this two-step LAGC process could allow us to efficiently prepare TC-OFN cocrystals in gram scale. The as-prepared cocrystals displayed the intrinsic green emission of TC with much higher photoluminescence quantum yield (13.75%) comparing with the pure solid TC with the almost-quenched emission (0.41%, aggregation-caused quenching (ACQ)). The ultrafast spectra study on these cocrystals verifies the successful barrier function of OFN molecules in interrupting the well-known singlet fission (SF) in TC solids. Furthermore, this method can allow us to easily fabricate fluorescent TC-OFN water inks, which can be employed to prepare luminescent paintings or highly emissive ultratransparent/flexible films.